Millenial Smart Farming: Integrated Agricultural Technology Innovation in Increasing Export Value of Agricultural Products to Young Farmers in Gobleg Village, Buleleng Regency - I Made Wimas Candranegara; Supranoto Supranoto; I Wayan Mirta (Iapa Proceedings Conference, 2022)
Problems in the food sector have always been a concern in every country. The government always strives to meet people's food needs and maintain food security, including through empowering farmers, encouraging millennial farmers, increasing productivity and using technology. The Millennial Smartfarming Program is an ecosystem for millennial empowerment through fostering and developing a digital agricultural ecosystem from upstream to downstream and increasing village financial inclusion. The program's objectives are to implement smart agriculture by implementing agricultural digitization with the Internet of Things (IoT), to form an agricultural ecosystem by opening market access to farmers, to strengthening millennial farmer institutions. The focus of this research is on young farmers in Gobleg Village, Buleleng Regency, considering that most of the people in this village depend on the agricultural sector. The urgency in this research is that currently the interest of the younger generation in agriculture is very minimal, inversely proportional to the extent of agricultural land in Gobleg Village, Buleleng Regency. The research method used is a qualitative research method with a focus on the millennial Smart Farming program. The results of this study are that there are already several successful millennial farmers, including the Self-help Agricultural and Rural Training Center [P4S] Keren Young Farmers [PMK] Gobleg Village, Buleleng Regency who have succeeded in exporting local agricultural products to foreign countries.